3D Image Reconstruction Using Force-Controlled Robot-Assisted Ultrasound Scanning - Furman, Anna; Rupprecht, Nick; Seßner, Julian; Franke, Jörg (2024 46th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2024)
Ultrasound (US) is a valuable tool for imaging anatomical structures and tissue characteristics due to its noninvasive nature, real-time imaging capabilities, and wide accessibility. Accurate positioning and defined application of pressure with the US probe play a significant role in US imaging. Robot-assisted US imaging can address these issues and additionally facilitate three-dimensional (3D) reconstruction of US images, providing a deeper understanding of tissue structures. Therefore, this paper focuses on the fundamental step of acquiring US images and reconstructing US volumes through the integration of a US system with a collaborative robot. The paper demonstrates that force-controlled images can be acquired with high accuracy and that 3D images can be accurately reconstructed to closely match real-world measurements. The utilization of the DICOM standard enhances the performance of robot-assisted 3D reconstruction in this preliminary phase by enabling image extraction and pose data embedding. Furthermore, tissue elasticity is a critical factor in various medical applications, and accurate measurement of tissue stiffness is essential for prosthesis fitting, requiring innovative approaches such as shear wave elastography (SWE) in addition to conventional US imaging. Therefore, this paper also lays the groundwork for future efforts in 3D reconstruction of SWE images with the aim of refining tissue modeling for prosthetic fitting and diagnostic